Scalable production of core–shell nanoparticles by flash nanocomplexation to enhance mucosal transport for oral delivery of insulin. Issue 7 (31st January 2018) - He, Zhiyu; Liu, Zhijia; Tian, Houkuan; Hu, Yizong; Liu, Lixin; Leong, Kam W.; Mao, Hai-Quan; Chen, Yongming
Abstract : Flash Nanocomplexation (FNC) as a scalable manufacturing method to facilitate successful clinical translation of protein therapeutics. Abstract : Scalable manufacturing continues to present a major barrier for clinical translation of nanotherapeutics. Methods available for fabricating protein-encapsulating nanoparticles in a scalable fashion are scarce. Protein delivery often requires multiple functionalities to be incorporated into the same vehicle. Specifically for nanoparticle-mediated oral delivery of protein therapeutics, protection in GI tract, site-specific release, facilitating transmucosal permeation, and enhancing epithelial transport are a few desirable features to be engineered into a nanoparticle system. Here we devised a sequential flash nanocomplexation (FNC) technique for the scalable production of a core–shell structured nanoparticle system by combining materials choice and particle size and structure to fulfill these functions, therefore enhancing the delivery efficiency of insulin. This method is highly effective in controlling the size, generating core–shell structure with high encapsulation efficiency (97%) and payload capacity (67%) using insulin/l -penetratin complex nanoparticles as a core coated with hyaluronic acid (HA). Both the in vitro and in vivo models confirmed that the HA coating on these core–shell nanoparticles enhanced the permeation of nanoparticles through the intestinal mucus layer and improved trans-epithelial absorption of insulin nanoparticles; and the enhancement effect was most prominent using HA with the highest average molecular weight. The insulin-loaded nanoparticles were then encapsulated into enteric microcapsules (MCs) in an FNC process to provide additional protection against the acidic environment in the stomach while allowing rapid release of insulin nanoparticles when they reach small intestine. The optimized multifunctional MCs delivered an effective glucose reduction in a Type I diabetes rat model following a single oral administration, yielding a relative bioavailability of 11% in comparison with subcutaneous injection of free-form insulin. This FNC technique is highly effective in controlling particle size and structure to improve delivery properties and function. It can be easily extended to oral delivery for other protein therapeutics.